Review: Potency of Secondary Metabolite Componds from Soursop (Annona murricata) and Sugar Apple (Annona squamosa) as Plant-Based Pesticides for Controling Pests and Diseases of Plants - Tando, Edi (University of Brawijaya, 2018)
Indonesia is one country that is rich will flora and fauna which are biological resources. Plant secondary metabolites is a resource that is used for drugs. Besides can be extracted directly from the plant, also can be synthesized to obtain chemical compounds or their derivatives, through the development of cell culture. The impact of the use of synthetic pesticides / chemicals have an impact that is not good for health and cause disruption of the ecological balance. This paper aims to determine the potential utilization of secondary metabolites in plant soursop (Annona murricata) and sugar apple (Annona squamosa) as botanical pesticides to control pests and plant diseases. Plants soursop (Annona muricata) and sugar apple (Annona squamosa) has potential as a pesticide plant in controlling pests and diseases in plants. Results of phytochemical screening on extracts of leaves of the soursop (Annona muricata) found secondary metabolites: alkaloids, flavonoids, terpenoids, coumarin and lactones, anthraquinone, tannins, glycosides, phenols, phytosterols, and saponins, while the detection of the presence of a group of chemical compounds in seed extracts Soursop ( Annona muricata) and sugar apple (Annona squamosa), found secondary metabolites: alkaloids, flavonoids, polyphenols, terpenoids, coumarin, steroids, lactones, anthraquinone, tannins, glycosides, and saponins cyanadin. Natural pesticides are reducing pests, but is not directly Plant Pest Organisms (PPO) pests quickly. Natural pesticide application with the correct dose, can reduce pests, reduce costs and be environmentally friendly.